2012
DOI: 10.1208/s12249-012-9878-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polysorbate 80 Concentration on Thermal and Photostability of a Monoclonal Antibody

Abstract: Abstract. Polysorbate 80 is widely used in protein formulations to protect protein against agitationinduced aggregation. In this study, we address concerns about residual peroxide present in Polysorbate 80 on protein stability. Residual peroxide may oxidize active pharmaceutical ingredients leading to reduced stability and may ultimately lead to lower potency and efficacy. The effect of Polysorbate 80 concentration on thermal and photostability of monoclonal antibody of the IgG1 subclass (MAb1) was evaluated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…Protein destabilising effects in increasing polysorbate concentrations have been observed in other studies (Agarkhed et al, 2013;Amand Bhaskar, 2014). In this study, no significant differences in aggregate formation were observed between the two PS-20 concentrations (Figure 2), although a higher concentration of silicone-oil droplets is observed in the 0.05% w/v concentration (Figures 3-4).…”
Section: Ps-20 Limits the Formation Of Aggregates In Siliconized Pfs supporting
confidence: 69%
See 1 more Smart Citation
“…Protein destabilising effects in increasing polysorbate concentrations have been observed in other studies (Agarkhed et al, 2013;Amand Bhaskar, 2014). In this study, no significant differences in aggregate formation were observed between the two PS-20 concentrations (Figure 2), although a higher concentration of silicone-oil droplets is observed in the 0.05% w/v concentration (Figures 3-4).…”
Section: Ps-20 Limits the Formation Of Aggregates In Siliconized Pfs supporting
confidence: 69%
“…There are numerous studies assessing the mechanisms of mAb aggregation (Li et al, 2011;Morris et al, 2009) and the effects of silicone-oil (Basu et al, 2013;Gerhardt et al, 2014;Jones et al, 2005;Weinbuch et al, 2013b) or polysorbate surfactants (Agarkhed et al, 2013;Khan et al, 2015) in influencing the aggregation process; such studies include novel methods to reduce in situ mAb aggregation in PFS (Depaz et al, 2014). However, the focus has been the larger sub-visible size range of particulates i.e.…”
Section: Common Termsmentioning
confidence: 99%
“…Other plausible explanation underlying peak volume loss can be the presence of transient attractive intermolecular protein interactions in NMR samples. Although no significant changes were observed in the global conformational stability of mAb and its Fab and Fc fragments upon the addition of polysorbates, conformational destabilization of proteins by polysorbates have been observed in other proteins 6871 . For example, PS20 has been shown to reduce the thermodynamic stability of human interferon-γ and darbepoetin 24,69 .…”
Section: Discussionmentioning
confidence: 91%
“…Increase in concentration of both factors resulted in decrease of papain activity which might be due to distruption of protective layer of pectin due to tween 80 as surface active agent. 21 Optimized formulation selected has 2.5 g papain, 0.5g clove oil, 2.5 g pectin, 2.5 g propylene glycol, 0.125 g tween 80, 0.0094 g potassium di-hydrogen phosphate, 0.032 g disodium hydrogen phosphate, 0.025g methyl paraben, 0.0025g propyl paraben which showed highest % activity of papain indicating its stability and viscosity of 7800cps due to which it can be easily retained on carious tooth cavity. Efficacy of developed formulation against bacterial infection and caries removal were important parameters of evaluation.…”
Section: Discussionmentioning
confidence: 99%